Analysis of Criminal Behavior through Clustering Approach - Yadav, Romika; Sheoran, Savita Kumari (International Journal of Computer Sciences and Engineering, 2025)
The spatio-temporal modeling of a social system play an important role in forecasting the future trend of that system. In this paper, we present an approach to model the past crime behavior for future crime prediction. The study considered major crime event from Haryana state and used clustering approach to predict future crime trend. The analysis results obtained on ‘R’ tool for the past few years are found inconformity with that of real time trend, which envisage the success of our model proposed in this paper